2021
DOI: 10.1007/s00442-021-05039-x
|View full text |Cite
|
Sign up to set email alerts
|

Niche lability mitigates the impact of invasion but not urbanization

Abstract: Native species can coexist with invasive congeners by partitioning niche space; however, impacts from invasive species often occur alongside other disturbances. Native species' responses to the interactions of multiple disturbances remain poorly understood. Here we study the impacts of urbanization and an invasive congener on a native species. Using abundance (catch-per-unit effort) and vertical distribution of native green anoles (Anolis carolinensis) and invasive brown anoles (Anolis sagrei) across a gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…• Niche plasticity/lability hypothesis: Species can adjust their vertical niche in pursuit of optimal conditions (microclimatic and/or resource; Basham et al, 2022) or as a compensatory response to disturbance (Borden et al, 2022;Neilly et al, 2018) • Arboreal trait syndrome: The amalgamation of physiological, behavioural and morphological adaptations to living above-ground generates a syndrome of traits (Scheffers & Williams, 2018). A similar hypothesis by Scheffers et al (2017) proposes that, as a consequence of this syndrome, arboreal species should also have higher dispersal potential which would increase resistance and resilience to both current and historical environmental instability, respectively.…”
Section: Future Direc Tionsmentioning
confidence: 99%
See 2 more Smart Citations
“…• Niche plasticity/lability hypothesis: Species can adjust their vertical niche in pursuit of optimal conditions (microclimatic and/or resource; Basham et al, 2022) or as a compensatory response to disturbance (Borden et al, 2022;Neilly et al, 2018) • Arboreal trait syndrome: The amalgamation of physiological, behavioural and morphological adaptations to living above-ground generates a syndrome of traits (Scheffers & Williams, 2018). A similar hypothesis by Scheffers et al (2017) proposes that, as a consequence of this syndrome, arboreal species should also have higher dispersal potential which would increase resistance and resilience to both current and historical environmental instability, respectively.…”
Section: Future Direc Tionsmentioning
confidence: 99%
“…Novel competitive interactions can also trigger shifts in vertical niche preferences. In northern Florida, USA, the brown anole Anolis sagrei , a non‐native, aggressive and understorey dwelling species, caused an 8.3 m shift in median perch height in the native green anole Anolis carolinensis (Borden et al, 2022). Overall competition likely plays an important role in forest diversity dynamics, particularly when there are strong similarities in food and habitat preferences.…”
Section: Ecological Patterns In Vertical Dimensions Across Space and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the relationship between anthropogenic habitat disturbance and the genotypes of hybrid green anoles, canopy cover and impervious surface area were selected as quantitative proxies of urbanization. These variables are commonly used as metrics of urbanization (Borden et al, 2022), are expected to be negatively correlated (i.e., canopy cover will be low and impervious surface area will be high in distinctly urban habitats), and are related to environmental temperatures relevant for lizards (Ackley et al, 2015;Battles & Kolbe, 2019;Kolbe et al, 2016). Using GPS coordinates for the site of capture of each hybrid individual, values for both variables were extracted from the 2016 US Forest Service Tree Canopy Cover and 2016 Percent Developed Imperviousness GIS layers produced by the National Land Cover Database (Yang et al, 2018).…”
Section: Environmental Association Analysismentioning
confidence: 99%
“…Anecdotally, local Hawaiians frequently told us that the brown anoles were displacing green anoles, despite the layman's inability to distinguish between a brown A. carolinensis and an A. sagrei may limit the reliability of these observations. Furthermore, if A. sagrei were displacing A. carolinensis to higher perches, as seen in the southeastern United States (Edwards and Lailvaux 2012; Stuart et al 2014;Borden et al 2022), this may cause A. carolinensis to be less visible to the casual observer even if they remained present at unchanging density. Experimental studies have also demonstrated that A. carolinensis' ability to colonize novel islands is apparently inhibited (if not prevented) by a co-invasion of A. sagrei (Losos and Spiller 1999) but given A. carolinensis' earlier colonization of Hawai'i, these phenomena may not be relevant in this system.…”
Section: Potential (Co-)drivers Of Morphological Changementioning
confidence: 99%